Gains attained in malaria control coverage within settings earmarked for pre-elimination: malaria indicator and prevalence surveys 2012, Eritrea. (December 2015) - Berhane, Araia; Mihreteab, Selam; Ahmed, Hagos; Zehaie, Assefash; Abdulmumini, Usman; Chanda, Emmanuel
Abstract Background Eritrea, like most countries in sub-Saharan Africa, has expended much effort towards malaria control with the view of transitioning from reduction of the disease burden to elimination. This paper reports on the level of achievement as highlighted by the follow-on, malaria-endemic area representative, survey that aimed to provide data and to assess progress on malaria indicators and parasite prevalence at household level across the country. Methods In 2012, data were collected using a two-stage stratified cluster random sample of 1887 households in 96 clusters (villages in rural areas and census enumeration areas in urban centers) during a malaria indicator and prevalence survey in Eritrea. The survey determined parasite prevalence in vulnerable population groups and evaluated coverage, use and access to malaria control services. Standardized Roll-Back Malaria Monitoring and Evaluation Reference Group household and women's questionnaires were adapted to the local situation and used for collection of data that were analysed and summarized using descriptive statistics. Results The results of the survey showed that 90 % (95 % CI 89–91) of households owned at least one mosquito net. The proportion of the population with access to an insecticide-treated net (ITN) in their household was 55 % (95 % CI 54–56). The utilization of ITNs was 67 % (95 % CI 65–70) for children under 5 years and 60 % (95 % CI 58–63) for pregnant women (OR: 0. 73(95 % CI 0.62–0.85); P = 0.52). Only 28 % (95 % CI 26–30) of households were covered by indoor residual spraying (IRS) the previous year with significant heterogeneity by zoba (Debub 50 % (95 % CI 45–54) vs Gash Barka 32 % (95 % CI 28–36); OR = 0. 47 (95 % CI 0.36–0.61), P = 0.05). Malaria parasite prevalence was low; 1.1 % (95 % CI 0.9–1.3) in the general population and 1.4 % (95 % CI 1.0–2.0) in children under five and 0.7 % (95 % CI 0.4–1.1) among women aged 15–49 years. Only 19 % (95 % CI 15–26) of children under five had fever in the 2 weeks preceding the survey, with 61 % (95 % CI 54.1–67.1) seeking treatment from a health facility. Data on knowledge levels show that 92 % reported that malaria is transmitted by mosquitoes, 92 % mentioned that the use of mosquito nets could prevent malaria, 47 % knew malaria prevention medication, 83 % cited fever as a sign and symptom of malaria, and 35 % had heard or seen malaria awareness messages. Conclusion Notwithstanding confounders, the observed low malaria parasite prevalence could be associated with malaria intervention coverage, access and utilization as well as high and equitable knowledge levels in the population. This indicates that Eritrea is on the right track towards pre-elimination. However, technical and infrastructure capacity should be strengthened to facilitate implementation, surveillance, monitoring, and evaluation.